2020
DOI: 10.3390/insects11090557
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Based Functional Genomics in Hemiptera

Abstract: RNA interference (RNAi) is a powerful approach for sequence-specific gene silencing, displaying tremendous potential for functional genomics studies in hemipteran insects. Exploiting RNAi allows the biological roles of critical genes to be defined and aids the development of RNAi-based biopesticides. In this review, we provide context to the rapidly expanding field of RNAi-based functional genomics studies in hemipteran insects. We highlight the most widely used RNAi delivery strategies, including microinjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 129 publications
(137 reference statements)
2
31
0
8
Order By: Relevance
“…The RNAi efficiency and the resulting phenotypes were variable in the target insect. These variations are reliant on several critical factors, such as the target gene transcript abundance, spatial and temporal expression profiles, and the protein stability and turnover rate of the target gene [ 33 , 34 ]. In H. cunea , we found that HcCht5 was highly expressed during molting, while its expression decreased by about 40–60 times during inter-molting ( Figure 2 C), suggesting the function of HcCht5 in the molting process.…”
Section: Discussionmentioning
confidence: 99%
“…The RNAi efficiency and the resulting phenotypes were variable in the target insect. These variations are reliant on several critical factors, such as the target gene transcript abundance, spatial and temporal expression profiles, and the protein stability and turnover rate of the target gene [ 33 , 34 ]. In H. cunea , we found that HcCht5 was highly expressed during molting, while its expression decreased by about 40–60 times during inter-molting ( Figure 2 C), suggesting the function of HcCht5 in the molting process.…”
Section: Discussionmentioning
confidence: 99%
“…Each method has advantages and disadvantages with respect to the required experimental logistics. For a discussion of traditionally used delivery methods, readers are directed to a recently published review 9 . Upon entry into the insect, one of the first requirements for initiating the RNAi mechanism is the presence of a functional RNAi machinery (Fig.…”
Section: Rnai In Hemipteran Insectsmentioning
confidence: 99%
“…RNAi-based studies in whiteflies show significant knockdown of a wide set of gene targets, with reviews by Kaur et al (2020) [119], Luo et al (2017) [24] and others (e.g., and references therein: [120][121][122][123][124][125][126][127][128]. The earliest RNAi in whitefly, B. tabaci, used dsRNA's of actin, BtSnap and chickadee [129].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of leafhoppers and planthoppers of economic importance are in the same taxonomic suborder Auchenorrhyncha [ 137 ]. Reviews on RNAi in hemipterans show increasing research and development across a growing number of these important leafhopper and planthopper vectors [ 123 , 138 , 139 ]. Examples include the Green Rice Leafhopper, Nephotettix cincticeps; laccase-2 gene knockdown in first instar nymphs [ 140 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation